Review of some Southeast Asian sawfly species (Hymenoptera: Tenthredinidae) described by Attila Haris - Wei, Meicai; Niu, Gengyun (Zootaxa, 2009)
Twenty Asian sawfly species described by Dr. Haris are reviewed. Seven new combinations are proposed: Corrugia sulawesiensis (Haris, 2006) comb. nov. transferred from Nesoselandria, Inea flavopedis (Haris, 2006) comb. nov. transferred from Neostromboceros, Allantus achterbergianus (Haris, 2006) comb. nov., transferred from Athlophorus, Yuccacia phongdiensis (Haris, 2006) comb. nov. transferred from Eutomostethus, Stethomostus bicoloritonkinensis (Haris, 2006) comb. nov. transferred from Monophadnus, Asunoxa alboapicalis (Haris, 2006) comb. nov. and Asunoxa malaya (Haris, 2006) comb. nov., both transferred from Eusunoxa. Thirteen new synonyms are proposed: Nesoselandria shanica Malaise, 1944 = Nesoselandria albotonkinensis Haris, 2006, syn. nov.; Edenticornia zhejiangensis Wei et Nie, 1998 = Neostromboceros gracilioides Haris, 2006, syn. nov., = Neothrinax nigrotonkinensis Haris, 2006, syn. nov.; Neostromboceros brevicellus Wei, 2003 = Neostromboceros alboclypeatus Haris, 2006, syn. nov.; Neothrinax corvina Malaise, 1944 = Neostromboceros pleuronotatus Haris, 2006, syn. nov.; Neostromboceros planifrons Wei, 1997 = Neostromboceros phuongensis Haris, 2006, syn. nov.; Abusarbidea infuscata Wei et Nie, 1999 = Abusarbidea bicoloristigmata Haris, 2006, syn. nov.; Rhoptroceros cyatheae (Wei et Wang, 1995) = Rhopographus vietnamensis Haris, 2006, syn. nov.; Athlophorus albocinctus Wei, 2002 = Athlophorus devriesi Haris, 2006, syn. nov.; Neostromboceros rufithorax Malaise, 1944 = Allantidea achterbergiana Haris, 2006, syn. nov.; Taxonus formosacola (Rohwer, 1916) = Indotaxonus flavissimus Haris, 2006, syn. nov.; Tenthredo malimilova Wei, 2005 = Tenthredo danangiensis Haris, 2006, syn. nov.; Tenthredo borneo Shinohara, 1998 = Tenthredo djampangensis Haris, 2006, syn. nov. Illustrations of Yuccacia phongdiensis (Haris, 2006) are provided as an example of the very rare sawfly genus Yuccacia.